2009
DOI: 10.1097/01.psn.0000356867.18220.73
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Injuries of the Upper Extremity—Expected Outcome and Clinical Examination

Abstract: Nerve injuries are common in trauma surgery and appear more frequently if the upper extremity is affected. The aim of this study is to estimate possible predictors of the outcome after nerve injury of the upper extremity and to demonstrate feasible tools to follow up postoperative nerve regeneration for the daily clinical practice. During January 2000 until December 2004, a total of 372 nerve lesions of the upper extremity have been treated in our clinic. Patient's age, site of nerve lesion, concomitant injuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 18 publications
0
35
0
5
Order By: Relevance
“…Investigator initiated studies with collagen conduits report positive outcomes as high as 89% to as low as 40%. 3,8,14,24 In a prospective study comparing conduits with direct repair and autograft, Weber et al reported positive results in 66% of digital repairs greater than 5 mm. 25 In a recent analysis of the literature, Isaacs et al concluded that as the gap size increases, the outcome of the repair becomes less predictable, which may help explain the large variation in outcomes with conduit repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Investigator initiated studies with collagen conduits report positive outcomes as high as 89% to as low as 40%. 3,8,14,24 In a prospective study comparing conduits with direct repair and autograft, Weber et al reported positive results in 66% of digital repairs greater than 5 mm. 25 In a recent analysis of the literature, Isaacs et al concluded that as the gap size increases, the outcome of the repair becomes less predictable, which may help explain the large variation in outcomes with conduit repairs.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review, Wangensteen and Kalliaine [109] reported on a large number of sensory nerve gaps of 2.5-20 mm repaired with collagen conduits in multiple body regions and concluded that clinically successful outcomes were only observed in 43% of the cases. A prospective cohort study was performed by Lohmeyer and colleagues in 2009 [110] in digital and palmar nerve gaps of 6-18 mm, and results showed meaningful recovery in 75% of patients. Later, in 2011, Taras et al [111] reported a 73% meaningful recovery in 5-to 15-mm isolated digital nerve lacerations repaired with collagen conduits.…”
Section: Collagenmentioning
confidence: 99%
“…die Auswertung der Einfl ussgröße Patientenalter auf die 2PD-und Monofi lamenttestwerte gesunder Nerven herangezogen. Unter Einbezug der nach Alter klassifi zierten Ergebnisse der Publikationen von Lohmeyer et al [ 13 ] und Mailänder et al [ 15 ] erfolgte eine ergänzende Auswertung der Alterskorrelation der Verteilung der Ergebnisse nach direkter Nervenkoaptation gemäß ASSH-Klassifi kation über die Gesamtaltersspanne von 0-85 Lebensjahren mithilfe des Korrelationskoeffi zienten nach Spearman.…”
Section: Patienten Undunclassified
“…Unter Einbezug der nach Alter klassifi zierten Ergebnisse der Publikationen von Lohmeyer et al [ 13 ] und Mailänder et al [ 15 ] an gesunder Seite sowie nach primärer Nervennaht ergab sich eine über die Altersspanne von 0-85 Jahren signifi kante Korrelation zwischen Alter und ASSH-Score nach Nervenrekonstruktion, mit schlechterer Sensibilität im Alter. Bereits zwischen erstem und zweiten Lebensjahrzehnt verschlechterte sich die Prognose der Sensibilitätsrückkehr nach Nervenkoaptation deutlich (p < 0,001).…”
Section: Patienten Undunclassified
See 1 more Smart Citation